Impacto da tecnologia assistiva na infância e na adolescência na perspectiva dos pais: uma revisão sistemática da literatura - Carvalho, Elis Souza de (Universidade Federal de São Carlos, 2021)
Introduction: Alternative Communication devices and Assistive Technology are used in order to favor the occupations of children and teenagers, promoting their independence and autonomy in daily life. However, the way in which the impact of these resources is perceived by family members and other professionals who work with these users is a topic of interest, as these factors are essential for the implementation to be carried out. Objective: This study sought to verify the impact of implementing Assistive Technology devices in childhood and adolescence described in national and international literature in the family context. Methodology: A systematic literature review was carried out in national and international journals in the last ten years, adopting as inclusion criteria the use of devices from Augmentative and Alternative Communication systems and/or other Assistive Technology equipaments, in addition to describing its implementation involving children and teenagers with the cooperation of family members and other interlocutors in the interventions. Results: 22 articles were included in the analysis and highlighted the importance of the professionals working together with the families of Assistive Technology users in order to favor its use and bring positive impacts on daily life. Discussion: Assistive Technology resources can be considered essential for children, teenagers and their families in carrying out their activities, as they are able to promote quality of life, care facilitation, relief from caregiver burden, participation in meaningful activities and inclusion of its users in different contexts when implemented in order to meet their goals, taking into account their wishes and family specificities. Conclusions and final considerations: The results highlighted the importance of the participation of children, teenagers, their families and other interlocutors in decision-making about which devices and systems should be implemented, as well as for their continuing education so that the devices used reach the objective of expanding the participation and independence of its users in the different contexts in which they are inserted.
Impact of assistive technology on childhood and adolescence from the perspective of parents: a systematic review of the literature
Keywords: Familia; Tecnologia Assistiva; Seleção; Family; Assistive Technology; Selection; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL